2016
DOI: 10.1177/0891243216642394
|View full text |Cite
|
Sign up to set email alerts
|

Social Inequalities, Empowerment, and Women’s Transitions into Abusive Marriages

Abstract: Extant sociological theories of gendered power within marriage focus on how social forces—such as gender inequality—shape women’s power within already established partnerships and subsequently affect their risk of intimate partner violence. Yet, inequitable social forces similarly shape women’s life conditions prior to and during the marital transition, with implications for women’s power in marriage. In Myanmar, gender relations between women and men historically have been touted as equitable and advantageous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…It is possible that women are more vulnerable to Table 1 Prevalence of mental distress a and median HSCL-10 score by socio-demographic and selected health-related factors among men and women 18-49-year-old citizens of Yangon Region, Myanmar (Continued) the socio-cultural risks, for example, a cultural belief that men have higher status relative to women, which have led to more depression among women [35,37,38]. In Myanmar, men have a dominated role as head of household, primary breadwinner and legal representative of the family [39]. Furthermore, women carry a heavier burden of household responsibility than men and that may predispose them to an increased risk of mental distress, for example, when the household has economic problems [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that women are more vulnerable to Table 1 Prevalence of mental distress a and median HSCL-10 score by socio-demographic and selected health-related factors among men and women 18-49-year-old citizens of Yangon Region, Myanmar (Continued) the socio-cultural risks, for example, a cultural belief that men have higher status relative to women, which have led to more depression among women [35,37,38]. In Myanmar, men have a dominated role as head of household, primary breadwinner and legal representative of the family [39]. Furthermore, women carry a heavier burden of household responsibility than men and that may predispose them to an increased risk of mental distress, for example, when the household has economic problems [35,38].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study among married Myanmar women stated that there are inequitable power relations within marriages in Myanmar society. According to this study, this resulted in practices of controlling behaviour by husbands regarding women’s social relations, economic resources and sexual agency; which then led to a high level of spousal violence among married women [ 11 ]. These authors suggested that the factor of ‘husband’s controlling behaviour’ should be highlighted in the prevention efforts regarding spousal abuse.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence on whether co-occurrence and intergenerational cycles of violence vary based on pivotal child and maternal events and life stages is limited. Yet, children experience age-dependent risks of child abuse, and a woman's transition through key life events, such as marriage and childbirth, are central to her and her children's health and wellbeing, including risk of IPV ( Administration for Children and Families, 2021 ; Miedema, Shwe, & Kyaw, 2016 , Yount et al, 2018 ; Yount et al, 2016 ). In low-income settings, 1 research on developmental stage specific intersections between child abuse and IPV can help to guide practitioners and policymakers toward priority opportunities for violence prevention.…”
Section: Author Notementioning
confidence: 99%